Nilai-Nilai Utama Karakter Spiritual Keagamaan dan Integritas dalam Kisah Al-Qur’an - Khairul Khalqi (FALASIFA : Jurnal Studi Keislaman, 2019)
Various dynamics in leadership that occur in Indonesia, human characters that are very different from one another that happened before, it is important to discuss various examples in the story that Allah described in the Qur'an that can be read for example. In this study using the literature method. In this research, we can understand the figures that describe God in the Al-Qur’an who have religious characteristics and figures who have integrity. This can be seen in the story of Lukman al-Hakim with the verdict which has the story of ma'rifatullah (monotheism) which is illustrated in several verses in the Koran, where Lukman teaches children not to associate partners with Allah and worship only for Allah, therefore can help prayers in accordance with the commands of Allah SWT. Then take a human who has the character of integrity (honest) the writer takes on the story of the Prophet Yusuf AS illustrated in the Al-Qur’an where the compilation is slandered by Zulaikha but he is always honest and never succeeded, so that he was the Prophet Yusuf AS, can be chosen according desire because of the honesty he has.